Pembuatan Cetak Paving Block Berbahan Plastik Dan Pasir - Siagian, Nusyirwan Said; Siregar, Ahmad Marabdi; Mukhtar, Muharnif; Siregar, Chandra Amirsyahputra (Rekayasa Material, Manufaktur dan Energi, 2022)
Plastic is a synthetic polymerization product material, plastic is very difficult to decompose where the degradation of the plastic itself usually takes decades by nature. According to the Ministry of Environment and Health and the Ministry of Industry, the amount of waste in 2016 reached 6.25 million tons per year. This makes plastic waste one of the causes of environmental pollution. Recycling plastic waste is a solution to the problem of plastic waste which is increasingly polluting the environment. Realizing the importance of plastic recycling. Then a recycling tool will be made or changing the shape of plastic to be more useful, such as recycling plastic into paving blocks. Recycling plastic waste into paving blocks is expected to be a solution to environmental pollution due to plastic waste. Therefore a paving block printing tool made from plastic and sand is designed and produced which can reach a temperature of 397 0C, the paving block printing machine can make paving blocks made from PVC (Polyvinyl Chloride) plastic waste or plastic pipes. This tool can melt as much as 1.2 kg of plastic waste, namely 1 (one) paving block made from plastic waste and sand. The resulting paving blocks are in the form of bricks with sizes according to SNI Number 03-0691-1998 with dimensions of 10 cm x 20 cm x 6 cm.